Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. Join them; it only takes a minute:

Sign up
Here's how it works:
  1. Anybody can ask a question
  2. Anybody can answer
  3. The best answers are voted up and rise to the top

Evaluate$$ \iint_R \left ( e^{-x-y} \right )dxdy, $$ where $R$ is the region in the first quadrant in which $x+y\leq 1$.

I think the first step is $$\int_{0}^{1}\int_{0}^{1-y}\left ( e^{-x-y} \right )dxdy $$but I am not sure about whether this step is correct or not.

Please tell whether my answer is correct or not and please solve it. Thank you.

share|cite|improve this question
Hint:$\int\int e^{-x-y}dxdy=\int e^{-x}\int e^{-y}dydx$ – BigM Mar 16 '14 at 15:05
Does the interval that I evaluated correct? – Biboo Chung Mar 16 '14 at 15:06
Yeah.its correct. – BigM Mar 16 '14 at 15:08
Thank you very much. – Biboo Chung Mar 16 '14 at 15:10
Thank you very much – Biboo Chung Mar 16 '14 at 15:19
up vote 1 down vote accepted

Being rigorous in the notation will help you. The domain is $x\ge 0$, $y\ge 0$ and $x+y\leq 1$ (or $0\le y\le 1-x$), i.e. a triangle. You see that when $x$ ranges in $[0,1]$, and $y$ ranges in $[0,1-x]$.

$\int^1_{x=0} e^{-x}(\int^{1-x}_{y=0}{e^{-y}dy})dx=\int^1_{x=0} e^{-x}(-e^{-y}|^{1-x}_{y=0})dx=\int^1_{x=0}e^{-x}(1-e^{x-1})dx=\int^1_{x=0}(e^{-x}-\frac{1}{e})dx=(-e^{-x}-\frac{x}{e})|^1_{x=0}=1-\frac{2}{e}$

share|cite|improve this answer

Hint. $$ \int_{0}^{1}\int_{0}^{1-y}\left ( \mathrm{e}^{-x-y} \right )dx\,dy =\int_0^1\left( \int_0^{1-y}\mathrm{e}^{-x}\,dx\right)\, \mathrm{e}^{-y}\,dy= \int_0^1\left(1-\mathrm{e}^{y-1}\right)\, \mathrm{e}^{-y}\,dy. $$

share|cite|improve this answer
Thank you very much – Biboo Chung Mar 16 '14 at 15:17

Your Answer


By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.